Dry‐Out Periods of Rain Sensors vs. Soil Dry‐Out: Water Saving Potential and Recommendations - Cardenas, B. (2020)
The objectives of this study were (i) to determine the seasonal dry‐out periods of two RSs; (ii) to estimate the dry‐out periods of three soil textures (sand, loam, and clay loam) through a soil water balance model using numerical flow equations; (iii) to compare the dry‐out period of these soil textures to the dry‐out period of two RSs; and (iv) to propose recommendations for increased or decreased RS dry‐out period, if any. Existing RS dry‐out data from previous studies performed in Central Florida were assembled along with hourly weather data to estimate hourly turfgrass evapotranspiration (ETc). Precipitation data were used with ETc to simulate soil dry‐out, using the WAVE 3.0 model. Modeled soil dry‐out times were compared against actual RS dry‐out data. The average RS dry‐out time was not different between the RS brands tested, which was around 19 h. The dry‐out time of the sand‐textured soil was different from the loam and clay loam, which were similar to one another. The dry‐out times of the soils modeled were always above 52, 75, and 89 h for sand, clay loam, and loam, respectively. Therefore, these results show that the RSs tested do not follow the dry‐out characteristics of any of the soil textures modeled. An electronic mechanism that could delay the RSs resuming to the allowing irrigation mode is recommended to the industry.